Inclusive learning: Perspectives on virtual exchange and global learning - Bryant, Abigail; de Moraes Garcia, Daniela Nogueira [UNESP]; Salomão, Ana Cristina Biondo [UNESP] (Springer Nature, 2023)
Considering the emergent needs involving the pandemic, virtual exchange continues to be relevant and a necessary strategy for internationalization in Higher Education. This chapter will explore the experience between the BRaVE Program at UNESP and the Educational Opportunity Program (EOP) at Jefferson Community College. The Arthur O. Eve Educational Opportunity Program is a New York State Legislative program introduced by Arthur O. Eve to provide access and opportunity for low-income students from historically disadvantaged backgrounds. Throughout a 5-week period, undergraduate students engaged in a virtual exchange opportunity called COIL (Collaborative Online International Learning). The experience helped provide scaffolding to learning and growing in the development of college students. We will also explore the importance of engaging students in global learning by encouraging joint tasks and utilizing digital technologies toward the democratization of knowledge, intercultural competence, and student success.
Keywords: Democratization of knowledge; Global learning; Inclusive learning; Internationalization; Virtual exchange